Kajian Arahan Penyediaan Ruang Kota Bagi Pedagang Kaki Lima di Kawasan Pendidikan Tembalang, Kota Semarang - Apriliasari, Nur Khasanah (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
Street vendors (PKL) are one of the informal sectors that are often viewed as a parasite sector and have a negative impact on the city's image. However, the existence of street vendors also become one of the highest city's economic support and provide benefits for the community. Rukmana (2008) states that street vendors are an integral form of urban transformation from their economic system, from agriculture-based society to industry and services. Thus, the informal sector including street vendors need to be considered in the provision of space in urban areas. Street vendors in the educational area of Tembalang increasingly mushrooming after the transfer of Undip Pleburan students to Tembalang. The street vendors use public spaces and interfere with other space users, especially pedestrians and road users. This research uses positivistic-rationalism approach with quantitative research method to determine the direction of city space provision for street vendors in Tembalang educational area. The result of this research is the provision of city space for street vendors in Tembalang Educational Area directed by arranging PKL activity on strategic and accessible road corridor. Provision of space for street vendors as stated in the Decree of Mayor of Semarang no. 511.3 / 16 2001 on Land Stipulation / Location PKL needs to be reviewed because it has not contain the characteristics and needs of street vendors and consumers. The capacity of the existing space has not been able to accommodate the needs of street vendors in Tembalang Education Area in the future.